The Effect of Belief, Halal Certification, and Food Safety on the Decision to Purchase Halal Food Products - Manurung, Jihan Salwaa Aqiilah; Isaskar, Riyanti; Aprilia, Anisa; Pratiwi, Destyana Ellingga (Universitas Mercu Buana, 2025)
Objectives: Based on the report of The Royal Islamic Strategic Studies Center (2022), Indonesia is one ofathe countries with the largest Muslim population in the world. The large number of Muslim population must of course be accompanied by guarantees ofasecurity, comfort, protection and legal certainty regarding the halalness of a product consumed.Methodology: The quantitative research approach used proportionate stratified random sampling of 100 research respondents from the population of high school students at Islamic boarding schools in Kisaran. The analysis was conductedausing a structural equation model, with SmartPLS 4.1 software.Finding: The results showed that beliefs cannot have a direct effect on purchase decisions. Purchase intention has a positive effect on purchase decisions. The findings also showed that other factors such as halal certification andafood safety have a positive impact on purchase decisions.Conclusion: It is important to obtain more information related to product halalness and halal certification for products, especially foods that do not yet have it. That halal certification and food safety can increase consumer purchasing interest and purchase decisions. This finding has implications for manufacturers to ensure that their products are halal certified, referring to the regulations set by the Ministry of Cooperatives and Small and Medium Enterprises of the Republic ofaIndonesia, namely the obligation for all MSME products to be halal certified and have guaranteed food safety.